PDL Progenitor–Mediated PDL Recovery Contributes to Orthodontic Relapse. (August 2016) - Feng, L.; Yang, R.; Liu, D.; Wang, X.; Song, Y.; Cao, H.; He, D.; Gan, Y.; Kou, X.; Zhou, Y.
Periodontal ligament (PDL) is subjected to mechanical force during physiologic activities. PDL stem/ progenitor cells are the main mesenchymal stem cells in PDL. However, how PDL progenitors participate in PDL homeostasis upon and after mechanical force is largely unknown. In this study, force-triggered orthodontic tooth movement and the following relapse were used as models to demonstrate the response of PDL progenitors and their role in PDL remodeling upon and after mechanical force. Upon orthodontic force, PDL collagen on the compression side significantly degraded, showing a broken and disorganized pattern. After force withdrawal, the degraded PDL collagen recovered during the early stage of relapse. Correspondingly, increased CD90 + PDL progenitors with suppressed expression of type I collagen (Col-I) were observed upon orthodontic force, whereas these cells accumulated at the degradation regions and regained Col-I expression after force withdrawal during early relapse. Our results further showed that compressive force altered cell morphology and repressed collagen expression in cultured PDL progenitors, which both recovered after force withdrawal. Force withdrawal–induced recovery of collagen expression in cultured PDL progenitors could be regulated by transforming growth factor–β (TGF-β), a key molecule for tissue homeostasis and extracellular matrix remodeling. More interesting, inhibiting the regained Col-I expression in CD90 + PDL progenitors by blocking TGF-β interrupted PDL collagen recovery and partially inhibited the early relapse. These data suggest that PDL progenitors can respond to mechanical force and may process intrinsic stability to recover to original status after force withdrawal. PDL progenitors with intrinsic stability are required for PDL recovery and consequently contribute to early orthodontic relapse, which can be regulated by TGF-β signaling.